Vitrification of Neat Semen Alters Sperm Parameters and DNA Integrity - Khalili, Mohammad Ali; Adib, Maryam; Halvaei, Iman; Nabi, Ali (Urology Journal, 2014)
Abstract <span style="font-size: 10.0pt; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Purpose: Our aim was to evaluate the effect of neat semen vitrification on human sperm vital parameters and DNA integrity in men with normal and abnormal sperm parameters. Materials and Methods: Semen samples were 17 normozoospermic samples and 17 specimens with abnormal sperm parameters. Semen analysis was performed according to World Health Organization (WHO) criteria. Then, the smear was provided from each sample and fixed for terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining. Vitrification of neat semen was done by plunging cryoloops directly into liquid nitrogen and preserved for 7 days. The samples were warmed and re-evaluated for sperm parameters as well as DNA integrity. Besides, the correlation between sperm parameters and DNA fragmentation was assessed pre- and post vitrification. Results: Cryopreserved spermatozoa showed significant decrease in sperm motility, viability and normal morphology after thawing in both normal and abnormal semen. Also, the rate of sperm DNA fragmentation was significantly higher after vitrification compared to fresh samples in normal (24.76 ± 5.03 and 16.41 ± 4.53, P = .002) and abnormal (34.29 ± 10.02 and 23.5 ± 8.31, P < .0001), respectively. There was negative correlation between sperm motility and sperm DNA integrity in both groups after vitrification. Conclusion: Vitrification of neat ejaculates has negative impact on sperm parameters as well as DNA integrity, particularly among abnormal semen subjects. It is, therefore, recommend to process semen samples and vitrify the sperm pellets.